Self-selection, Export Market Heterogeneity and Productivity Improvements: Firm Level Evidence from Slovenia - Jože P. Damijan; Sašo Polanec; Janez Prašnikar (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
This paper adds a new dimension to the recent literature on relationship beween firm's heterogeneity in tfirms of productivity and its decision to exports and/or invest in foreign affiliate, namely the heterogeneity of foreign markets. Exploiting a rich and complete dataset for Slovenian exporting firms in the period 1994 - 2002, we gain several interesting insights. First, we demonstrate the importance of fixed entry costs in foreign markets causing that the number of foreign markets served by individual firm increases with firm's productivity level. We show that firms enter additional export markets only gradually - on average one market in two years. Second, we demonstrate that, on average, exporting firms are not always more productive than firms supplying only domestic market. Also, we confirm a conjecture that higher productivity level is required for firms starting to export to advanced countries as opposed to starting to export to developing countries. Finally, we observe that firms can gain significant productivity improvements when serving foreign markets. Significant productivity improvements occur only when serving advanced, high-wage foreign markets. In a small open country, exporting per se does not warranty such effects.
Keywords: D24; F14; 330; Exports; Productivity; Firm Heterogeneity; Export Market Heterogeneity; Direktinvestition; Multinationales Unternehmen; Produktivität; Auslandsmarkt; Slowenien